DIAGNOSIS KIAI DALAM MENGENAL CIVITAS PESANTREN (Studi Analisis Kepemimpinan Situasional di Pondok Pesantren Bustanul Falah Banyuwangi) - Fanani, Ahmad Aziz; Wahyono, Imam (INCARE, International Journal of Educational Resources, 2021)
In the midst of individualistic nature and materialistic lifestyles that are increasingly thickening, Islamic boarding schools are still consistent by presenting an education system that is able to bridge the physical (physical) needs and mental spiritual (spiritual) needs of humans. The uniqueness of the role of pesantren is certainly inseparable from the professionalism and intelligence of the Kiai in leading the pesantren education community. It is at this point that the main reason for this research is raised. The main focus in the discussion of this research focuses on the Kiai's way of diagnosing the pesantren community. The focus in this research is how the behavior of the kiai in diagnosing the pesantren community. This research was conducted at the Bustanul Falah Islamic boarding school in Banyuwangi using a qualitative approach to describe the leadership behavior of Kiai. The conclusion of the findings based on the results of in-depth interviews, documentation and observations illustrates that the Kiai's dialogue process carried out in the internal and external environment of Islamic boarding schools is about adjusting three important components to the work needs of developing formal education in pesantren. The three are religious compatibility, commitment and competence.